2016
DOI: 10.1002/14651858.cd012483
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative neuromonitoring versus visual nerve identification for prevention of recurrent laryngeal nerve injury in adults undergoing thyroid surgery

Abstract: This is a protocol for a Cochrane Review (Intervention). The objectives are as follows:\ud To assess the effects of intraoperative neuromonitoring (IONM) versus visual nerve identification for prevention of recurrent laryngeal\ud nerve injury in adults undergoing thyroid surgery

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
49
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 40 publications
1
49
1
2
Order By: Relevance
“…On the other hand, a large meta‐analysis with 64 699 nerves at risk showed no benefit . In addition, a recent Cochrane review showed no significant benefit …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…On the other hand, a large meta‐analysis with 64 699 nerves at risk showed no benefit . In addition, a recent Cochrane review showed no significant benefit …”
Section: Discussionmentioning
confidence: 96%
“…By contrast, other experts have suggested that the routine use of IONM is not supported by the literature . There have been no randomized control trials demonstrating any benefit in the reduction of RLN injury . Indeed, false‐positive signal loss may result in inappropriate abandonment of procedures and subsequent increased costs to the community.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is no evidence that the use of I-IONM reduces the incidence of RLN injury during thyroid surgery. One possible explanation for this is that I-IONM does not provide real-time feedback about RLN or VN function during surgical maneuvers [10]. On the other hand, C-IONM is an ideal modality to monitor the intactness of the RLN and the VN because it offers real-time feedback to surgeons.…”
Section: Discussionmentioning
confidence: 99%
“…It is our group's opinion that, from a scientific point of view, we should go past the mantra that neuromonitoring prevents either unilateral or bilateral palsy and focus on its many other potential advantages.…”
mentioning
confidence: 99%